IDENTIFICATION OF NEW MEDIA AESTHETIC ARTIFICIAL INTELLIGENCE FILM - Sugiarto Sugiarto; Santi Widiastuti (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Main Objective: This study checks the different intersections of film and Artificial Intelligence (AI), and trial and error is needed to re-check the state of “new media” (NM). This study’s purpose is to identify of subversion of the creator duty, the media and instrument of creative activities, and the aesthetics subsequent from the identity of the developing Artificial Intelligence film. Background problem: AI is composed to take the film industry by the cyclone, its application helps streamline production practices, and its increasing work in film scripting and visuals convolutes the notion and function of creations and the aesthetics of NM. Novelty: By analyzing how three films were co-written with Artificial Intelligence arranged with “Foucault's theory” of the duty of the creator or producer, and the aesthetics and state of current NM, this research establishes an identity for the cinema form of Artificial Intelligence films. Research Method: This study uses a qualitative exploratory methodology to combine various perspectives that are developing on new media streams where this research is crossing 2 major areas in Film & Media, and Artificial Intelligence & Machine Learning. Finding/Result: Patterns discovered as curated data sets reveal trends in cinematic narratives, opening the door for a more creative agency. Artificial Intelligence films transcend the boundaries of technological convergence, offering a more essential way to recognize the special behavior and opportunity of NM forms as self-reflective and demonstrating the versatility of film. Conclusion: This research makes Artificial Intelligence films an emerging media with a different tendency from the media and is directly related to its contribution. By involving the theorization of NM technology and its developmental tuff simultaneously, Artificial Intelligence films are presented as an inventive design of film in phrases of digital production, virtual placement, historical preoccupation, and producer duty.